ANALISA STRATEGI MENINGKATKAN DAYA TARIK WISATAWAN GUNUNG MERAPI DI BASECAMP MERAPI JEEP ADVENTURE KEDUNGSRITI (MJAK) - Astuti, Andri Yuni; Nugroho, Putut Jito (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This study aims to analyze (1) the potential and attractiveness of tourism, (2) tourist perceptions of tourist attractions, and (3) strategies for increasing the attractiveness of Mount Merapi and MJAK ADVENTURE. This study uses quantitative descriptive research. Data collection was conducted using observation, questionnaires, and documentation at MJAK ADVENTURE. The study involved 30 respondents, who were visitors to MJAK ADVENTURE. Descriptive analysis was used to determine assessment scores and aspects requiring improvement. The results show that strategies for increasing the attractiveness of Mount Merapi Jeep Adventure Kedungsriti (MJAK) tourists, including facilities, attitudes and behaviors, and services, were rated moderate by the majority (57%). Several weaknesses requiring improvement include: 1) cleanliness and comfort of facilities, 2) neatness of employee appearance, 3) customer trust in employees, 4) tour guides, and 5) punctuality of service.